HCV infection and drug use in Italian detainees: results of validation of EQDP (Eu-ropean Questionnaire on Drug Use in Prison) - Nava, Felice Alfonso; Nava, Felice Alfonso (Acta Biomedica Atenei Parmensis, 2018)
Purpose:  the aim of this paper is to describe the results of a survey conducted in Italy amongst detainees by administering a specific questionnaire (EQDP, European Questionnaire on Drug Use in Prison), in order to investigate drug use in prison, any sharing of used needles and, lastly, the degree of self-awareness regarding health (more specifically, in terms of HIV, HBV and HCV infection). Structure of the article: the article is split into three parts. The first provides an overview of the methodological guidelines for the EQDP, which were issued in March 2017 by the European Monitoring Centre for Drugs and Drug Addiction. The second describes the structure of the EQDP questionnaire (Italian version). The third provides the results of a survey conducted in Italy using this questionnaire and the health-related implications for the prison community, in particular regarding HCV, HIV and HBV.Results: the data were collected by the self-administration of the questionnaire to groups of a sample consisting of 40 male detainees under in normal prisons. In this type of custody, fewer subjects were substance abusers during previous prison terms than amongst subjects in open prisons. The most common forms of dependence (tobacco, alcohol, THC, cocaine, psychostimulants, hallucinogens, opioids, sedatives) detected were significantly different between the two types of imprisonment and they were easier to identify in the open-prison system. The analysis of the state of health with regard to the above viruses demonstrated that, in open-prison conditions, a higher percentage of subjects have been tested for HIV, HBV and HCV, whereas detainees in normal prison conditions were almost all unaware of their infection status and had a poorer awareness of their health in general. Conclusions: health status (HBV, HCV, HIV) is not declared amongst normal detainees, who are less aware of their health conditions and receive less risk-reduction intervention. Amongst open-prison detainees, however, all substance users are subject to risk reduction interventions, which are efficacious in improving self-awareness in terms of a greater use of blood tests and treatments for infectious diseases.